1997
DOI: 10.1136/hrt.78.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in chronic heart failure is related to the aetiology of heart disease

Abstract: Objective-To assess whether the underlying aetiology of chronic heart failure is a predictor of exercise performance. Setting-Tertiary referral centre for cardiology. Patients and outcome measuresRetrospective study of maximum exercise testing with metabolic gas exchange measurements in 212 patients with chronic heart failure who had undergone coronary angiography. Echocardiography and radionucleide ventriculography were used to determine indices of left ventricular function, and coronary arteriography was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Rather, we found that both absolute and percentage predicted values of peak VO 2 were strikingly reduced in patients with LBBB compared with those without, and to a lesser extent by CAD (19), even when exercise tolerance was not limited by acute ischemia. Patients with neither LBBB nor CAD thus had the highest absolute and percentage predicted values of peak VO 2 , whereas those with LBBB had the lowest values of all, irrespective of whether CAD was present or not.…”
Section: Discussionmentioning
confidence: 72%
“…Rather, we found that both absolute and percentage predicted values of peak VO 2 were strikingly reduced in patients with LBBB compared with those without, and to a lesser extent by CAD (19), even when exercise tolerance was not limited by acute ischemia. Patients with neither LBBB nor CAD thus had the highest absolute and percentage predicted values of peak VO 2 , whereas those with LBBB had the lowest values of all, irrespective of whether CAD was present or not.…”
Section: Discussionmentioning
confidence: 72%
“…In a retrospective analysis Clark et al [10] showed that patients with heart failure due to non-ischemic heart disease have a higher peak VO2 than patients with coronary artery disease; this did not appear to be related to any difference in ventilatory response to exercise, as measured by the VE/VCO2 slope. However, in this study the role of etiology was not assessed independently of the degree of left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…However, for the same level of left ventricular dysfunction, different degrees of exercise impairment are found [7][8][9]. Few previous reports have proposed that the etiology of heart failure might influence functional capacity, regardless of left ventricular function, through being related to different levels of peripheral vascular disease, skeletal muscle myopathy and cardiac adaptation to excessive wall stress [10,11]. Therefore, the aim of the present study was to examine the effect of heart failure etiology on peak VO2 and on the ventilatory response to exercise in a large cohort of unselected patients with CHF.…”
Section: Introductionmentioning
confidence: 91%
“…It is interesting that the etiology of HF (ischemic/dilated cardiomyopathy) is an independent predictor of peak VO 2 and VE/VCO 2 slope but not of AT, although all of these exercise variables differ significantly when comparing patients with ischemic or dilated cardiomyopathy. 5 Clark et al 19 have reported these differences in peak VO 2 . The worsened CPX variables (lower peak VO 2 , lower AT, and higher VE/VCO 2 slope) found in the ischemic HF patients compared with the ones in the nonischemic group may be attributed to changes in the cardiac muscle and function occurring because of ischemia in this group.…”
Section: Individual Variable Multiple Variable (Stepwise)mentioning
confidence: 96%